2013
DOI: 10.3892/ijmm.2013.1382
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of Src in the nucleus of myocytes in cardiac hypertrophy

Abstract: The Src kinase is involved in signaling events leading to cardiac hypertrophy. The exact effects of tyrosine phosphorylation and subnuclear distribution on cardiac hypertrophy and failure remain to be investigated. In this study, we examined the intranuclear expression and distribution of c-Src, Src phosphorylated at tyrosine 529 (Src[pY529]), Src phosphorylated at tyrosine 418 (Src[pY418]) and Src phosphorylated at tyrosine 215 (Src[pY215]) in the myocardial nuclei of the left ventricle (LV) from 2-, 6-, 12- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…MS-mediated autophosphorylation of Src is highly associated with ERK1/2 activation [14]. Recent study revealed the expression and distribution of Src in the nucleus of cardiomyocytes with hypertrophy [15], and β-arrestin2 enhanced nuclear localization of ERK1/2 via GPCRs activation [16]. Mutant AT1 receptor lacking the docking site impaired Src-dependent nuclear translocation of ERK1/2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…MS-mediated autophosphorylation of Src is highly associated with ERK1/2 activation [14]. Recent study revealed the expression and distribution of Src in the nucleus of cardiomyocytes with hypertrophy [15], and β-arrestin2 enhanced nuclear localization of ERK1/2 via GPCRs activation [16]. Mutant AT1 receptor lacking the docking site impaired Src-dependent nuclear translocation of ERK1/2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of sympathetic nerve activation, the intertwined processes of apoptosis, hypertrophy, proliferation, and other cellular fates need to be further elucidated. In addition to the aforementioned limitations, it is worth noting that the phosphorylation of Src and its subcellular distribution play a role in signal transduction within the myocardial nucleus, representing an important process in cellular response to external stimuli [ 52 ]. Meanwhile, ERK1/2, as a crucial intracellular mediator, exerts profound effects on cell proliferation, survival, apoptosis and transdifferentiation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Src kinase, a non-receptor protein tyrosine kinase, plays important roles in cell proliferation, adhesion, survival, differentiation, and cell motility [31]. It is involved in a variety of signal pathways involved in cardiac hypertrophy, such as G protein coupled receptor signal transduction and integrin mediated [32]. The activity of Src kinase can be regulated by changing the phosphorylation of specific tyrosine residues.…”
Section: Discussionmentioning
confidence: 99%